Dossier - Digital Literature in English: an Intercultural/Transliterary Approach - Maria Goicoechea de Jorge (Texto Digital)
Texto Digital is aimed at encouraging discussion and reflection about literature in digital media. The English language has been a forerunner in the dissemination of digital textualities and their literary possibilities. The July issue 2012 will be dedicated to present the current state of digital literature in English, with special emphasis placed on works or readings which bring to the fore the blurring of cultural and literary boundaries. Our transliterary approach invites reflection on literary proposals which transcend particular literary traditions and cultures, using their digital nature to make the blurring of boundaries effective. We promote a comparative literature perspective which underscores, not the differences and demarcations, but the fusions, the borrowings, the mixtures which overflow cyberspace and form its characteristic virtual landscapes.